2015
DOI: 10.2522/ptj.20130590
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of the Canadian Occupational Performance Measure in Participants With Tendon Injury and Dupuytren Disease

Abstract: The results supported the hypotheses and, thus, the construct validity of the COPM after surgery in people with hand conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 50 publications
1
28
1
1
Order By: Relevance
“…Our findings are consistent with previous reports that Dupuytren’s patients’ assessments of their symptoms and function do not correlate with QuickDASH and other standardised measurements, and support the use of patient-specific outcome measures in this population 10 13 14 18. However, the absence of correlation does not negate the usefulness of objective measures, when using PVS, but argues for including them based on the knowledge that they report on non-overlapping aspects of DC and its treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings are consistent with previous reports that Dupuytren’s patients’ assessments of their symptoms and function do not correlate with QuickDASH and other standardised measurements, and support the use of patient-specific outcome measures in this population 10 13 14 18. However, the absence of correlation does not negate the usefulness of objective measures, when using PVS, but argues for including them based on the knowledge that they report on non-overlapping aspects of DC and its treatment.…”
Section: Discussionsupporting
confidence: 90%
“…The QuickDASH may have not been very responsive for Dupuytren’s because we excluded its optional sports module. The patient-specific COPM was developed in 1993, and it has been validated for Dupuytren’s 18. The PVS is similar to the COPM with regard to activity choice and rating, but unlike the COPM, which requires a semi-structured interview with a trained occupational therapist, PVS does not require any person other than the patient him/herself to provide information about their health state 25.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As hypothesized, we found that the SPPB scores were moderately correlated with the quadriceps strength measurement and only slightly correlated with the handgrip strength measurement. It is well known that bodily functions, such as muscle strength, are related to functional activities, 1 , 2 , 19 , 27 partly because a certain amount of strength is necessary for the satisfactory completion of most functional activities. From this perspective, and because the activities in the SPPB rely mostly on lower-extremity strength, we expected the SPPB scores to be more highly correlated with quadriceps strength than with handgrip muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Os dinamômetros hidráulicos, amplamente utilizados na clínica de Terapia Ocupacional, fornecem ao seu usuário unicamente a informação sobre a força máxima alcançada durante o teste de esforço isométrico máximo, não se mostram, por tanto, capazes de registrar outros parâmetros associados à expressão de força, tais como a manutenção da força e seu tempo de sustentação. O uso de força máxima de preensão prediz apenas 37% do desempenho das atividades cotidianas (VEN-STEVENS et al, 2015), sendo fundamental para tais as sustentações de posições ao longo de todo o período das tarefas, utilizando para tanto (em detrimento da força máxima), a força de resistência, que por sua vez não pode ser mensurada pelos dinamômetros hidráulicos.…”
Section: Resultsunclassified